Displaying Wages as an Indicator of the Social Responsibility of Business in Accounting and Reporting - Katkova Natalia V.; Burlan Svitlana A.; Maslova Kateryna V. (Bìznes Inform, 2017)
The article is concerned with displaying wages in both accounting and reporting, in the context of social responsibility. The basic approaches to definition of social responsibility in the context of relations of employers and employees were considered. It was noted that an effective means of implementing the conception of social responsibility would be the preparation of integrated reporting, and for this purpose the elements of social responsibility of enterprises should be reflected in the accounting system. It is expedient to include in the indicators of social responsibility of the integrated reporting of enterprises the level of remuneration of the current character; the amount of compensation payments in connection with the completion of work and due to difficult working conditions, harmful industries; the amount of incentive payments as a result of developing the skill level and increasing labor efficiency; payments on the sectoral individual pensions and on social support programs, etc. The displaying of the proposed indicators in the reporting of enterprise would provide disclosure of information on the implementation of the principles of social responsibility and would inform the interested parties about the implementation of social programs and projects at the enterprise.